Współpraca adwokatów z sądami kościelnymi - Białobrzeski, Tomasz (Ius Matrimoniale, 2018)
For over ten years, lawyers have been cooperating with church courts in Poland. It resulted in rich experience. All the time, however, there is a need to improve this cooperation in order to better serve the parties in marital processes. This publication is an attempt to draw attention to certain aspects of this cooperation. The issues addressed concern the following topics: requirements for advocates; pre-trial consultation; attempt to reconcile the parties; choosing the right court; court costs; order of handling cases; the way of file storage; exchange of court correspondence.